2017
DOI: 10.1049/iet-pel.2015.0864
|View full text |Cite
|
Sign up to set email alerts
|

Particle swarm optimisation‐based modified SHE method for cascaded H‐bridge multilevel inverters

Abstract: Low-frequency switching strategies are considered as an effective way of achieving efficient performance in multilevel inverters. Selective harmonic elimination (SHE) is a modulation technique of this category which gives a superior outcome suppressing low-order detrimental harmonics. Limited number of decision variables offered by SHE in the corresponding non-linear equations hinders obtaining high-quality waveforms. Current research is targeted on two distinct objectives for cascaded H-bridge inverters. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…Currently SHE technique is being prominently used to synthesize output voltage of multilevel inverters [5,27,33]. By applying Fourier series analysis, the staircase output voltage of cascaded multilevel inverter with non-equal DC sources can be described as [15]:…”
Section: Optimization Methods For Selected Harmonic Elimination (She)mentioning
confidence: 99%
See 4 more Smart Citations
“…Currently SHE technique is being prominently used to synthesize output voltage of multilevel inverters [5,27,33]. By applying Fourier series analysis, the staircase output voltage of cascaded multilevel inverter with non-equal DC sources can be described as [15]:…”
Section: Optimization Methods For Selected Harmonic Elimination (She)mentioning
confidence: 99%
“…Inverter having equal steps was considered in the work of [15]; however, some investigators may try to provide an optimization of voltage levels of unequal magnitude as shown in Figure 8 as per reference [12]. Output waveform pattern with unequal DC source of single phase 9-level CHB-MLI is shown in Figure 8.…”
Section: Photovoltaic Based Chb-mli Configuration and Switching Schemementioning
confidence: 99%
See 3 more Smart Citations